666 EFFECT OF PERINDOPRIL ON PHYSICAL PERFORMANCE, MUSCLE MASS AND QUALITY OF LIFE IN OLDER PEOPLE WITH SARCOPENIA: RESULTS: FROM THE. (8th March 2022) - Witham, M D; Adamson, S; Avenell, A; Band, M M; Donnan, P T; George, J; Hapca, A; Hume, C; Kemp, P; McKenzie, E; Pilvinyte, K; Smith, K; et al.
Abstract: Introduction: Angiotensin-converting enzyme inhibitors such as perindopril have been proposed as treatments to improve muscle mass and physical performance but have not been tested in randomised controlled trials enrolling patients with sarcopenia. Methods: We conducted a placebo-controlled, parallel group, double-blind, randomised two-by-two factorial trial. Participants aged 70 and over with low muscle mass by bioimpedance and either low grip strength or low walk speed, were recruited from 14 UK sites. Participants were randomised to receive one year of perindopril 4 mg once daily or matching placebo, and to receive leucine powder 2.5 g three times a day or matching placebo. The primary outcome was the between-group difference in the Short Physical Performance Battery, measured at baseline, 6 and 12 months, analysed using repeated-measures mixed models. Secondary outcomes included grip strength, quadriceps strength, six-minute walk distance, appendicular muscle mass measured by dual x-ray absorptiometry, quality of life measured using the EQ5D tool, falls rates and adverse events. Results: We screened 320 people and randomised 145 participants, mean age 79 (SD 6) years; 78 (54%) were women and the mean SPPB was 7.0 (SD 2.4). 73 were randomised to perindopril and 72 to placebo. Median adherence was lower for perindopril (76% vs 96%; p < 0.001). Perindopril had no significant effect on the primary outcome (adjusted treatment effect −0.1 points [95%CI -1.2 to 1.0]). No significant treatment effect was seen for any secondary outcome except for worse EQ5D thermometer scores in the perindopril group (treatment effect −12 points [95%CI -21 to −3]). More adverse events were seen in the perindopril group (218 vs 165) but falls rates were similar (perindopril 2.0 [95%CI 1.1 to 3.0] per year; placebo 2.8 [95%CI 0.6 to 5.1] per year). Conclusion: Perindopril did not improve measures of physical performance, muscle mass or quality of life in older people with sarcopenia.